IMPLEMENTATION OF CONSULTATION SERVICE AND EFFECT TO THE CONSULTEE’S SATISFACTION (An Evaluation Study of The Implementation Counseling Service and Satisfaction of Client) - M. Ismail Makki; Alfaiz Alfaiz; Asroful Kadafi; Yunita Dwi Setyoningsih; Hengki Yandri (JURNAL KONSELING GUSJIGANG, 2018)
In counseling service, there are many type of counseling in it’s practice, the one of the type was a counsultation service. This type of counseling service was help the consultee to solve a problem of the other people that need their help, this can be implemented if consultee can solve their own problem,. This service always implemented in school setting, this because of a counseling in school will help like parents, or another student to help their kids or their friends in learning process. But in reality of counseling practice was far from the ideal. How is the school consultation service in Indonesia implemented? and what are the problems? is a question that needs to be answered. This paper tries to answer the question with the method of analysis of research results with qualitative and also seek a satisfaction of consultation service. there are three researches on consulteeng services that have been done in three cities, namely Semarang, Padang and Banjarmasin. The research finds three categories of service implementation, is good, moderate and sufficient. The barriers found are low support from counsultte  and misunderstood the concept of consulteeng services. The effort to overcome the problem is with the improvement of quality of counselor which facilitated by MGBK. Dalam pelayanan konseling, adanya banyak jenis pelayanan konseling, salah satunya adalah pelayanan konsultasi. Jenis pelayanan konseling ini membantu konsulti untuk memecahkan masalah dari orang lain yang membutuhkan masukan darinya. Hal ini bisa diimplementasikan jika konsulti sudah bisa memecahkan masalahnya sendiri. Pelayanan ini selalu bisa diimplementasikan dalam seting sekolah, hal ini karena konseling disekolah akan membantu dan banyak berhadapan dengan seperti orang tua siswa, wali siswa, siswa yang membutuhkan kiat untuk anak dan teman sebayanya dalam proses belajar. Akan tetapi, realitanya praktek konseling masih jauh dari yang seharusnya. Bagaimana pelayanan konsultasi  sekolah di Indonesia di laksanakan ? dan apa saja permasalahnnya? merupakan pertanyaan yang perlu di jawab. Tulisan ini mencoba menjawab pertanyaan tersebut dengan metode analisis hasil penelitain dengan kualitatif dan kuantitatif dan juga menlihat kepuasan dari pelayanan konsultasi. terdapat tiga Riset tentang layanan konsultasi yang pernah di lakukan di tiga kota, yakni Semarang, Padang dan Banjarmasin. Hasil riset menemukan tiga kategori pelaksanaan layanan, yakni baik, sedang dan cukup. Hambatan yang di temukan berupa rendahnya dukungan dari counsultte dan salah memahami konsep layanan konsultasi. Upaya mengatasi masalah tersebut adalah dengan  peningkatan mutu konselor yang di fasilitasi oleh MGBK